Effectiveness of shortwave diathermy in patients with chronic low back pain: A study protocol for a randomised, single-blinded, multicentre clinical trial - Mohammad Ali; Saddam Hossain; MD. Abu Bakar Siddiq; Monirul Islam (PLoS ONE, 2026)
Background Chronic low back pain (CLBP) is a leading cause of disability worldwide and a major public health concern in low- and middle-income countries such as Bangladesh. Although international guidelines classify shortwave diathermy as a low-value treatment, it remains widely used in physiotherapy practice. Evidence on the effectiveness of continuous shortwave diathermy (CSWD) for CLBP is limited and inconsistent. This study aims to determine whether CSWD, when combined with standard physiotherapy, provides additional benefits compared with sham CSWD plus physiotherapy. Methods This multicentre, randomised, single-blind, sham-controlled trial will recruit 208 participants aged 18–65 years with CLBP from tertiary hospitals and physiotherapy clinics in Dhaka, Bangladesh. Participants will be randomly allocated (1:1) to receive CSWD or sham CSWD, each combined with a standardised physiotherapy programme delivered three times weekly for four weeks. The intervention group will receive active CSWD (27.12 MHz, continuous mode, 20 min/session), while the control group will receive sham treatment. Primary outcomes include back pain intensity, leg pain intensity (0–10 numerical rating scale), and activity limitation (Oswestry Disability Index). Secondary outcomes include the Brief Pain Inventory, Global Rating of Change, Satisfaction with Treatment, DASS-21, Insomnia Severity Index, Treatment Credibility Questionnaire, and healthcare utilisation. Outcomes will be assessed at baseline, 4, 12, and 24 weeks. Data will be analysed using an intention-to-treat approach with linear mixed-effects models. Discussion This trial will provide high-quality, context-specific evidence on the clinical and cost-effectiveness of CSWD for CLBP in a resource-constrained setting. The findings will inform physiotherapy practice in Bangladesh and may guide the appropriate use or de-implementation of this commonly used modality. The rigorous sham-controlled design will also contribute to the broader evidence base on electrotherapy for chronic pain.